Postoperative Urinary Retention With Gross Vulvar Edema After Use of 4% Icodextrin. Issue 7 (1st July 2015) - Reed, Beverly; Robinson, Randal
ABSTRACT: Background: 4% icodextrin is a fluid that can be instilled laparoscopically to prevent adhesion formation. There are few complications reported in the literature associated with its use. Case: A 38-year-old woman, gravida 2, para 0, abortus 2 underwent laparoscopic salpingectomy. 4% icodextrin was instilled in an effort to prevent adhesion formation. Postoperatively, the patient experienced urinary retention and gross vulvar edema that required foley catheter use until the 4% icodextrin solution had absorbed. Conclusion: Postoperative complications that may be associated with the use of 4% icodextrin include urinary retention and vulvar edema.